Penerapan Balut Tekan sebagai Strategi Penanganan Awal Perdarahan Vulnus Laceratum di IGD Puskesmas Liwuto Kota Baubau - Achmad Rinaldi Erman; Yusrah Taqiyah; Muhajirin Muhajirin; Akbar Asfar (Rumah Sakit Ibnu Sina, Makassar, 2025)
Laceration wounds (vulnus laceratum) may cause pain and external bleeding, requiring prompt initial management to prevent excessive blood loss. One simple early bleeding control strategy is direct pressure maintained with a pressure dressing. This case report describes the use of a sterile pressure dressing in a male patient (Mr. L) with a left plantar foot wound due to glass injury, accompanied by pain and active bleeding, presenting to the emergency unit of Liwuto Primary Health Center, Baubau. Data were obtained through clinical observation, brief interview, and review of available medical records/procedure sheets. Pain was assessed using the Numeric Rating Scale (NRS), while bleeding outcome was operationalized using bleeding status (active/controlled), dressing status (wet/dry), and time to hemostasis. After sterile pressure dressing application and 4-hour monitoring, pain decreased from NRS 8 to 3, and active bleeding was no longer observed at the 4-hour evaluation. These findings indicate clinical improvement in this case, but interpretation is limited by single-case design (n=1) without controls, incomplete quantitative serial bleeding documentation, and potential confounding from concomitant interventions (e.g., analgesics).